2013
DOI: 10.1111/vde.12017
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nuclear factor of activated T cells in granulocyte–macrophage colony‐stimulating factor production in canine keratinocytes stimulated with a cysteine protease

Abstract: The results suggest that GM-CSF production mediated by the cysteine protease is regulated not only by NFAT but also by unknown signalling pathways in canine keratinocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Based on what has been published to date, they are adherent, proliferative, capable of differentiation, express similar protein markers to primary keratinocytes and have been used to recreate stratum corneum in vitro. 8,25,26,[28][29][30][31][32] Using both ELISA and immunocytochemistry, we could not detect any MHC II protein in CPEKs. This protein has been detected in primary and immortalized keratinocytes of several species, including mice, rats and humans, [13][14][15]33,34 and in canine skin biopsies, where its expression was increased in cutaneous lesions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Based on what has been published to date, they are adherent, proliferative, capable of differentiation, express similar protein markers to primary keratinocytes and have been used to recreate stratum corneum in vitro. 8,25,26,[28][29][30][31][32] Using both ELISA and immunocytochemistry, we could not detect any MHC II protein in CPEKs. This protein has been detected in primary and immortalized keratinocytes of several species, including mice, rats and humans, [13][14][15]33,34 and in canine skin biopsies, where its expression was increased in cutaneous lesions.…”
Section: Discussionmentioning
confidence: 78%
“…We chose this cell line because of its phenotypic characteristics similar to those of primary keratinocytes. Based on what has been published to date, they are adherent, proliferative, capable of differentiation, express similar protein markers to primary keratinocytes and have been used to recreate stratum corneum in vitro …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GM‐CSF production was suppressed by addition of a cysteine protease inhibitor, suggesting that its production was most likely mediated via PAR‐2 by Der f 1, which is one of the major allergens and a cysteine protease . Similar to Der f 1, papain, a naturally derived cysteine protease, also induced GM‐CSF production with translocation of nuclear factor of activated T cells (NFAT) in CPEK, and production was partially inhibited by ciclosporin . These results suggest that GM‐CSF production in CPEK activated via PAR‐2 may be regulated not only by NFAT, but also by another transcription factor, such as nuclear factor‐kB (NF‐kB) or activator protein‐1 (AP‐1).…”
Section: Keratinocyte‐derived Chemokines and Cytokines That Are Direcmentioning
confidence: 86%
“…93 Similar to Der f 1, papain, a naturally derived cysteine protease, also induced GM-CSF production with translocation of nuclear factor of activated T cells (NFAT) in CPEK, and production was partially inhibited by ciclosporin. 94 These results suggest that GM-CSF production in CPEK activated via PAR-2 may be regulated not only by NFAT, but also by another transcription factor, such as nuclear factor-kB (NF-kB) or activator protein-1 (AP-1). A recent study demonstrated that IL-17A, a typical Th17 cytokine, also induced the transcription of gm-csf in CPEK.…”
Section: Keratinocyte-derived Cytokines and Chemokinesmentioning
confidence: 91%